Individualism in Spirituality?: A Close Look at Vedanta Students and Yoga Practitioners in Rio de Janeiro - dos Guimarães Bastos, Cecilia (International journal of Latin American religions, 2022)
The practices of yoga and meditation are discussed based on the observation of a group of Vedanta students and yoga practitioners. This article offers a critical reflection of the individualism inherent to the understanding of spirituality. In contrast to most studies that differentiate spirituality from religion, this research confirms that interlocutors tend to submit to religious dogmas and to authorities, in the form of the guru, the tradition and the cosmic order. It was noticed that they adapt to these principles, at the same time that they seem to transcend their individuality when becoming part of these holistic traditions, both as transmitters and receivers, who thus express their most significant values and meanings. These as a result challenge the concepts of autonomy and free choice.